2016
DOI: 10.1007/s10951-015-0466-5
|View full text |Cite
|
Sign up to set email alerts
|

The local–global conjecture for scheduling with non-linear cost

Abstract: We consider the classical scheduling problem on a single machine, on which we need to schedule sequentially n given jobs. Every job j has a processing time p j and a priority weight w j , and for a given schedule a completion time C j . In this paper we consider the problem of minimizing the objective value j w j C β j for some fixed constant β > 0. This non-linearity is motivated for example by the learning effect of a machine improving its efficiency over time, or by the speed scaling model. For β = 1, the w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Indeed, without any restrictions on h, it is a difficult to believe anything can be said in general. If there are no precedence constraints and h(C j ) = C β j , β ≥ 0, this is the problem 1|| w j C β j , as studied in [10], in which it is shown that the problem of minimizing total weighted completion time plus total energy requirement (see [17,37]) can be reduced to 1|| w j C β j , β ∈ (0, 1). We discuss the problem 1|| w j h(C j ) further in Subsection 2.4, in which we bound the approximation ratio of our algorithm by a simple expression in terms of h.…”
Section: Motivation Examples and Previous Workmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, without any restrictions on h, it is a difficult to believe anything can be said in general. If there are no precedence constraints and h(C j ) = C β j , β ≥ 0, this is the problem 1|| w j C β j , as studied in [10], in which it is shown that the problem of minimizing total weighted completion time plus total energy requirement (see [17,37]) can be reduced to 1|| w j C β j , β ∈ (0, 1). We discuss the problem 1|| w j h(C j ) further in Subsection 2.4, in which we bound the approximation ratio of our algorithm by a simple expression in terms of h.…”
Section: Motivation Examples and Previous Workmentioning
confidence: 99%
“…We may also consider the more specific problem 1|| w j h(C j ) for some non-decreasing function h. In [37], a polynomial time approximation scheme is given for the problem. If h(C j ) = C β j for β = 1, then it is the problem considered in [10]. It is unknown whether there exists a polynomial time algorithm to compute an optimal schedule for this problem, or if it is NP hard (see [10] and the references therein).…”
Section: Applications To Schedulingmentioning
confidence: 99%
See 1 more Smart Citation
“…Following a long series of improvements [2,6,12,15,16], Drr and Vsquez [7] conjectured that for all cost functions of the form f j (t) = w j t β , β > 0 and all jobs i, j, i ≺ l j implies i ≺ g j. Latter, Bansal et al [4] confirmed this conjecture, and they also gave a counter example of the generalized conjecture that i ≺ l[a,b] j implies i ≺ g[a,b] j. For airplane refueling problem, Vsquez [17]…”
Section: Related Workmentioning
confidence: 99%